One of our kind : a novel [large type] - Yoon, Nicola (Random House Large Print, 2024)
"When Jasmyn and King Williams move their family to the planned Black utopia of Liberty, California, they hope to find a community of like-minded people, a place where their growing family can thrive. King settles in at once, embracing the Liberty ethos, including the luxe wellness center at the top of the hill, which proves to be the heart of the community. But Jasmyn struggles to fit in. She expected to find liberals and social justice activists striving for racial equality, but Liberty residents seem more focused on spa treatments and keeping up appearances. Jasmyn's only friends in the community are equally perplexed and frustrated by Liberty's outlook, a frustration that turns to concern when their loved ones start embracing the Liberty way of life. As Jasmyn learns more about Liberty and its founders, she discovers a terrible secret that threatens to destroy her world in ways she could never have imagined"--